Animal Cell Education Media in high school based on Virtual Reality - Ibrahim Ramdani, Muhammad Aslam (Faculty of Engineering, Universitas Brawijaya, 2020)
Educational media is one of the tools used for learning. Some examples of educational media are books, videos, audio, objects, and images. Since the first time the use of books as educational media is a must in the school area, but UNESCO said Indonesia was second from the bottom of the matter of world literacy, meaning that interest in reading was very low. According to UNESCO data, the reading interest of Indonesian people is very alarming, only 0.001%. That is, out of 1,000 Indonesians, only 1 person is avid reader. To increase interest in reading it is necessary to have an appropriate and interesting educational media for children. One way is through the application of technology to educational media, active smartphone users in Indonesia in 2018 around 177.9 million people, the biggest contributor comes from the age category of children and adolescents. Hope parents allow their children to play smartphones for educational purposes.Interactive education media can be designed with the support of technology. This research is conducted in the hope that it can provide learning options for children other than books, but using educational media that applies technology in them, so that children can be interested in learning, so that the purpose of this application is to improve children's learning outcomes can be achieved.